Enhancing Employee Performance through Human Capital and Educational Management: Evidence from a State Detention Center - Moch. Akbar Dwiyanto; Kusmiyanti (Al-Qalam Institue, 2026)
Human resources are a strategic asset that fundamentally determines organizational success across both public and private sectors. Effective management and development of human capital are essential for enhancing institutional performance and sustaining organizational competitiveness. This study investigates the impact of human capital on employee performance at the State Detention Center. Using a quantitative approach, data were collected from 80 employees selected through probability sampling based on the Krejcie and Morgan formula. A structured questionnaire consisting of 46 items was administered via Google Forms. Data analysis, conducted using IBM SPSS version 25, involved normality tests, simple linear regression, significance tests, and determination analysis. The findings reveal that human capital significantly influences employee performance (p = 0.000 < 0.05), with an R-square value of 0.715, indicating that 71.5% of performance variance is explained by human capital. The study underscores the crucial role of continuous learning, competency development, and educational management strategies in optimizing workforce performance within correctional institutions. These results provide valuable insights for human resource and educational managers to design more effective training and development programs that foster professional growth and institutional excellence.